Implementation of Hajj Manasik Guidance Management at the Ministry of Religious Affairs Office of Sragen Regency - Novitasari, Hesty; Yuliar, Ade (Munazzama: Journal of Islamic Management and Pilgrimage, 2023)
The research aims to determine the general description of the implementation of Hajj ritual (manasik) guidance by the Ministry of Religious Affairs of Sragen Regency for prospective Hajj pilgrims. The research was descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results showed that the implementation of guidance on mass Hajj manasik of the Ministry of Religious Affairs of Sragen Regency was aligned with the planning that had been formed and in accordance with the Decree of the Director General of Hajj and Umrah Implementation No. 164 of 2023 concerning guidelines for organizing Hajj manasik guidance for regular pilgrims at the Regency or City and District levels. The Ministry of Religious Affairs of Sragen Regency used four management functions in carrying out Hajj manasik guidance activities: planning, organizing, implementing and supervising.